2013
DOI: 10.7547/1030016
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Ipsilateral or Contralateral Foot Disorders and Hand Dominance

Abstract: Background To our knowledge, hand dominance and side of foot disorders has not been described in the literature. The purpose of the current study was to evaluate whether hand dominance was associated with ipsilateral foot disorders among community-dwelling older men and women Methods Data were from the Framingham Foot Study (n=2,089, examined 2002–2008). Hand preference for writing was used to classify hand dominance. Foot disorders and side of disorders were based on a validated foot examination. Generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unfortunately, the scope of our study did not permit such examination. To our knowledge, only one study reported association of handedness with HAV (Nguyen et al, 2013). They found that left handed people were more likely to have HAV on the left foot.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, the scope of our study did not permit such examination. To our knowledge, only one study reported association of handedness with HAV (Nguyen et al, 2013). They found that left handed people were more likely to have HAV on the left foot.…”
Section: Discussionmentioning
confidence: 92%
“…Historical control data, when available, was abstracted from the medical literature. [14][15][16][17][18][19][20][21] Given the low number of male patients recruited and the potential for sex-related differences in physical examination features, only data for the female cohort are presented. A p-value <0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%